2016
DOI: 10.1038/ni.3491
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic CDR3 residues promote the development of self-reactive T cells

Abstract: Studies of individual T cells receptors (TCRs) have shed some light on structural features that underlie self-reactivity. However, general rules that predict whether TCRs are self-reactive have not been fully elucidated. Analyses of thymocytes expressing all Vβ family members show that the interfacial hydrophobicity of amino acids at positions 6 and 7 of the CDR3β segment robustly promotes the development of self-reactive TCRs. An index based on these findings distinguishes Vβ2+, Vβ6+ and Vβ8.2+ regulatory T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
174
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(199 citation statements)
references
References 53 publications
24
174
1
Order By: Relevance
“…This lack of difference suggests that our measure of selection is mainly sensitive to basic selection against misfolding of the encoded receptor protein (which would have the same effect on thymic and blood repertoires) and is relatively insensitive to thymic selection against self-recognizing receptors (which would be present in blood but not in thymus). Negative selection in the thymus of course exists, but previous work on statistically characterizing its nature has shown that strong effects are localized in the few residues that actually contact presented peptides (33)(34)(35). Because we are statistically characterizing selection across the more extensive CDR3 region (11 aa long on average), it is perhaps not surprising that localized negative selection effects are washed out.…”
Section: Significancementioning
confidence: 94%
“…This lack of difference suggests that our measure of selection is mainly sensitive to basic selection against misfolding of the encoded receptor protein (which would have the same effect on thymic and blood repertoires) and is relatively insensitive to thymic selection against self-recognizing receptors (which would be present in blood but not in thymus). Negative selection in the thymus of course exists, but previous work on statistically characterizing its nature has shown that strong effects are localized in the few residues that actually contact presented peptides (33)(34)(35). Because we are statistically characterizing selection across the more extensive CDR3 region (11 aa long on average), it is perhaps not surprising that localized negative selection effects are washed out.…”
Section: Significancementioning
confidence: 94%
“…Nur77 expression has been used to readout functionality of CD4+ T cells in multiple systems29303132333435. Even though these T cells are functional, it does not describe the role these T cells are playing in the immune response.…”
Section: Resultsmentioning
confidence: 99%
“…The different conclusion from the aforementioned TCR repertoire analyses 26 may relate to the different analytical approaches used to assess tTreg cell selection–intrathymic injection of TCR-expressing thymocytes 36 vs comparison with thymic TCR repertoires 26 . The conclusions may also be affected by the different TCRβ chains used 26, 36 or the use of a limited TCRα/fixed TCRβ model 26 , as effects on Treg cell selection has been reported for changes in a single TCR chain (TCRα 37 ). The ability of two of these colonic TCRs (CT2/CT6) to facilitate pTreg cell induction from naïve T cells in the periphery in normal mice was confirmed via the generation of transgenic (Tg) lines 33 .…”
Section: Developmental Origin Of Colonic Treg Cellsmentioning
confidence: 99%